2021
DOI: 10.1093/jas/skab080
|View full text |Cite
|
Sign up to set email alerts
|

Ancient grains as novel dietary carbohydrate sources in canine diets

Abstract: Ancient grains are becoming an increasingly abundant carbohydrate source in the pet food market as a result of their popularity and novelty in the human market. Thus, it is imperative to evaluate the characteristics of these ingredients in vivo. Ten adult intact female beagles were used in a replicated 5x5 Latin square design. Five dietary treatments were evaluated containing either: rice (CON), amaranth (AM), white proso millet (WPM), quinoa (QU), or oat groats (OG). All diets were formulated to include 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Previous studies comparing inclusion of whole grains in dog food are scarce. However, in studies on dogs, alpha and beta diversity have been reported to be unaffected both when comparing different ancient grains, one of which was oat groats 8 , and when comparing rye flour to fermented rye or cornmeal added to a vegetarian diet supplemented with feather meal 7 . Effects on fecal microbiota of consumption of whole-grain rye and wheat have been compared in a human study 26 , which found no significant effects on microbial alpha or beta diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies comparing inclusion of whole grains in dog food are scarce. However, in studies on dogs, alpha and beta diversity have been reported to be unaffected both when comparing different ancient grains, one of which was oat groats 8 , and when comparing rye flour to fermented rye or cornmeal added to a vegetarian diet supplemented with feather meal 7 . Effects on fecal microbiota of consumption of whole-grain rye and wheat have been compared in a human study 26 , which found no significant effects on microbial alpha or beta diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in dogs have investigated potential promotion of a healthy gut microbiota by specific dietary fiber types 1 3 , fiber-rich food by-products, or fiber blends added to the food 4 6 . However, few studies have investigated how gut microbiota composition and function are affected by addition of fiber as part of the whole-grain component in dog food 7 , 8 . Whole grains contain several bioactive compounds, such as tocols, phytosterols, alkylresorcinols and other phenolic compounds, which can have additive or even synergistic effects with the gut microbiota on host health according to studies in humans and pigs 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those of Freel et al, who reported that the feeding of defatted BSFL meal (5%, 10%, or 20%) and BSFL oil (2.5% or 5%) for 4 weeks did not affect food intake or BW in adult beagle dogs [ 18 ]. In addition, although the focus was not fermented oat, Traughber et al reported that feeding a diet containing 40% oats did not affect food intake or BW compared with the dogs fed a diet containing 40% rice [ 37 ]. Moreover, in dogs fed a diet containing 25% barley, which has a composition similar to oats, there was no effect on daily intake, preference ratio, nutrient digestibility, or stool scores compared to those with a diet containing 25% rice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies on rodents and poultry, researchers have also assessed the intestinal flora-associated effects of quinoa in a range of other hosts. For example, Traughber et al evaluated the effects of five ancient grains (including rice and quinoa) as carbohydrate sources on blood glucose and insulin levels in dogs ( 73 ). The intestinal flora of animals in the quinoa group were found to be characterized by an increase in the relative abundance of Bacteroidetes , and these authors established that diets comprising up to 40% of these grains, would have beneficial effects on overall host health, without adversely influencing nutrient digestibility, and had no significant effects on the levels of blood glucose or insulin in healthy dogs.…”
Section: The Regulatory Effects Of Quinoa Bioactive Components On Int...mentioning
confidence: 99%